2021
DOI: 10.26434/chemrxiv-2021-38gkc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coadsorption of NRR and HER intermediates determines the performance of Ru-N4 towards electrocatalytic N2 reduction

Abstract: Efficiency of the electrochemical N2 reduction reaction (NRR) to ammonia is seriously limited by the competing hydrogen evolution reaction (HER) but our current atomic-scale insight on the factors controlling HER/NRR competition are unknown. Herein we unveil the elementary mechanism, thermodynamics, and kinetics determining the HER/NRR selectivity on the state-of-the-art NRR electrocatalyst, Ru-N4 using constant potential density functional theory calculations (DFT). The calculations show that NRR and HER inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Inspired by an experimental study showing that single-atom Ru anchored on N-doped graphene (Ru−N 4 ) exhibited the highest NRR performance, 107 Wu et al modeled the Ru−N 4 electrocatalyst to unravel the mechanism, thermodynamics, and kinetics of NRR and competing HER reactions using grand canonical ensemble density functional theory (GCE-DFT). 108 The results suggested that both NRR and HER intermediates can be coadsorbed on the catalyst but that NRR intermediates significantly suppress the HER activity. Overall, it was emphasized that single-Mo-embedded N-doped graphene is a potential NRR electrocatalyst.…”
Section: Single-atom/cluster-decorated Metal-based Electrocatalystsmentioning
confidence: 99%
“…Inspired by an experimental study showing that single-atom Ru anchored on N-doped graphene (Ru−N 4 ) exhibited the highest NRR performance, 107 Wu et al modeled the Ru−N 4 electrocatalyst to unravel the mechanism, thermodynamics, and kinetics of NRR and competing HER reactions using grand canonical ensemble density functional theory (GCE-DFT). 108 The results suggested that both NRR and HER intermediates can be coadsorbed on the catalyst but that NRR intermediates significantly suppress the HER activity. Overall, it was emphasized that single-Mo-embedded N-doped graphene is a potential NRR electrocatalyst.…”
Section: Single-atom/cluster-decorated Metal-based Electrocatalystsmentioning
confidence: 99%
“…Taking the surface Pourbaix diagram into consideration, DPD MoMo−py has a wide potential range (−0.94 to −0.06 V) to adsorb *N 2 without being competed by *H adsorption, and at this potential range, it offers superior NRR activity with a potential of −0.19 V. These findings might benefit the way for diporphyrins to be employed as inspiration for the design and discovery of selective and active NRR electrocatalysts. Future work exploring the explicit dependence of pH and applied potential for the reaction via grand canonical DFT 50 can be done to achieve a more detailed understanding of NRR.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…34 Despite this, issues still exist. Two main causes hinder the design of highly efficient N 2 -to-NH 3 catalysts: the low activity toward the activation of inert N 2 as a result of the rather high bonding energy (945 kJ mol −1 ) between the very strong N�N bond; 35 and facing the competitive hydrogen evolution reaction (HER) from the proton adsorption under a high reduction potential, the unsatisfactory NRR selectivity, 36 causing rather low NH 3 yields and extremely inferior Faradaic efficiency. Although considerable efforts have been devoted to developing, optimizing, or designing electrocatalysts for artificial NRR, the discovery of candidates simultaneously possessing the high activity and selectivity under mild conditions remain a major challenge.…”
Section: Introductionmentioning
confidence: 99%